1998
DOI: 10.1093/brain/121.11.2067
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of flumazenil-PET versus [18F]fluorodeoxyglucose-PET and MRI in refractory partial epilepsy. A prospective study in 100 patients

Abstract: We assessed the clinical utility of [11C]flumazenil-PET (FMZ-PET) prospectively in 100 epileptic patients undergoing a pre-surgical evaluation, and defined the specific contribution of this neuro-imaging technique with respect to those of MRI and [18F]fluorodeoxyglucose-PET (FDG-PET). All patients benefited from a long term video-EEG monitoring, whereas an intracranial EEG investigation was performed in 40 cases. Most of our patients (73%) demonstrated a FMZ-PET abnormality; this hit rate was significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
1
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(160 citation statements)
references
References 0 publications
9
140
1
10
Order By: Relevance
“…This is in line with the literature, which reports that temporopolar blurring is present in 32‐66% of adults with TLE and HS39 and in 57% of children 42. It has previously been postulated to be caused by vasculometabolic changes,43 cortical dysplasia,44 inflammatory changes,45 increased perivascular spaces, abnormal water content,46 widespread gliosis45 as well as myelin loss 45. A recent study by Garbelli and colleagues relating histopathology to high‐field imaging carefully attempted to disentangle these factors and found that blurring was associated with axonal degeneration and reduced axonal numbers in the white matter 39.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the literature, which reports that temporopolar blurring is present in 32‐66% of adults with TLE and HS39 and in 57% of children 42. It has previously been postulated to be caused by vasculometabolic changes,43 cortical dysplasia,44 inflammatory changes,45 increased perivascular spaces, abnormal water content,46 widespread gliosis45 as well as myelin loss 45. A recent study by Garbelli and colleagues relating histopathology to high‐field imaging carefully attempted to disentangle these factors and found that blurring was associated with axonal degeneration and reduced axonal numbers in the white matter 39.…”
Section: Discussionmentioning
confidence: 99%
“…did not specify the type of EEG used in all patients. 102 A combination reference standard where patients received a variety of reference tests was considered acceptable. All studies avoided differential verification bias, but partial verification bias was a potential problem in three studies.…”
Section: Excluded (N = 7) Nomentioning
confidence: 99%
“…102 The final study reported that EEG was used as the reference standard without providing further details; therefore, it was unclear whether an appropriate reference standard had been used. 31 Partial verification bias did not appear to be a problem in any of these studies.…”
Section: 106mentioning
confidence: 99%
See 1 more Smart Citation
“…La génération de divers types cellulaires via un processus de division asymétrique qui sépare inégalement les déterminants cellulaires est un mécanisme conservé dans l'évolution, depuis Caenorhabditis elegans et Drosophila melanogaster [8,9] Figure 1A). La phosphorylation endogène a-t-elle un rôle fonctionnel ?…”
Section: Magazineunclassified